2017
DOI: 10.19044/esj.2017.v13n24p322
|View full text |Cite
|
Sign up to set email alerts
|

Changement De Couverture Forestière Dans Le Département De La Likouala (République Du Congo) Durant La Période De 1986 À 2015

Abstract: A study on the change of forest cover was carried out in the Department of Likouala, Republic of Congo for the period from 1986 to 2015. It was intended to calculate the areas of the different land conversions in the study period, but also to identify the causes of deforestation and forest land Landsat TM (1986), Etm + (2001), and Oli (2015) images were treated with the method of supervised classification "Maximum Likelihood" was applied to obtain the different maps of land type. The results revealed the lost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…. The study conducted byBouetou-Kadilamio, Averti Ifo, and Binsangou (2017) revealed considerable confusion between the degraded forest, crop-fallow and plantation classes. In their classifications, 31.1% and 34.11% of pixels in the crop-fallow and plantation classes in 1986 were assigned to the degraded forest class.…”
mentioning
confidence: 99%
“…. The study conducted byBouetou-Kadilamio, Averti Ifo, and Binsangou (2017) revealed considerable confusion between the degraded forest, crop-fallow and plantation classes. In their classifications, 31.1% and 34.11% of pixels in the crop-fallow and plantation classes in 1986 were assigned to the degraded forest class.…”
mentioning
confidence: 99%